Content analysis of thesis studies on disabled individuals in the field of sports science between 2014-2024 in Turkey - Simsek, S. E.; Demir, H.; Becan, S.; Tugcu, D. R. (Turkish Journal of Sport and Exercise, 2025)
This study aims to analyze the thesis studies on individuals with disabilities in the field of sport sciences in Turkey between 2014-2024 from various perspectives. In addition, this study is important in terms of contributing to the development of policies that support the participation of individuals with disabilities in sports. Document analysis, one of the qualitative research methods, was used in the study. The population of the study consists of all master's and doctoral theses completed in the field of sport sciences in Turkey between 2014 and 2024 in the National Thesis Center of the Council of Higher Education. The sample consists of 211 theses selected from this population in accordance with the research criteria and having full text access. The data were analyzed by content analysis according to the variables of thesis year, type, obstacle group, sample size, sample group, research type, department, university and data collection tools. As a result of the research, it was determined that the theses were concentrated especially in 2019 and 2024, master's theses were predominant, and individuals with physical disabilities were the most frequently studied group. While quantitative methods and survey scales are at the forefront methodologically, the limited use of qualitative and mixed methods points to gaps in the in-depth understanding of disabled people's experiences of participation in sport. Sample sizes are generally small to medium and studies on visually impaired individuals are the least represented. The theses were mostly produced in physical education and sport departments and were distributed across 47 different universities. The study reveals that the focus on individuals with physical disabilities is linked to the popularity of Paralympic sports, but the needs of other disability groups are not adequately addressed. Increasing qualitative methods, large-scale and interdisciplinary studies are recommended for future research.